Teachers’ and educators’ perspectives on systems thinking and its implementation in Dutch biology education - Gilissen, Melde G.R.; Knippels, Marie-Christine P.J.; Verhoeff, Roald P.; van Joolingen, Wouter R. (Journal of Biological Education, 2020)
Systems thinking, the ability to reason about systems in abstract terms, fosters students’ coherent understanding of biology. This study aimed to determine to what extent the integration of systems thinking in Dutch biology education is in line with perspectives from systems theories and experts. We related the perspective on systems thinking of systems biologists (n = 7) to those of biology teachers (n = 8) and educators (n = 9). The resulting perspectives were interpreted in terms of three systems theories, General Systems Theories (GST), Cybernetics and Dynamical Systems Theories (DST). Thirdly, we determined to what extent and how teachers and educators pay attention to systems thinking in their teaching practice. This was all done by the use of open-ended interviews and online questionnaires. The results show that the systems biologists and teacher educators involved implicitly refer to three systems theories, whereas the teachers refer to the GST and cybernetics only. Despite this, the results suggest that the implementation of systems thinking in Dutch pre-service teacher training and secondary biology education falls short of expectations. These outcomes underline the importance of teacher (educator) professional development on teaching systems thinking to bridge the gap between research and teaching practice.
Publisher: Routledge _eprint: https://doi.org/10.1080/00219266.2019.1609564
Keywords: Systems thinking; biology education; coherent understanding; professional development; secondary education